2000
DOI: 10.1093/brain/123.3.585
|View full text |Cite
|
Sign up to set email alerts
|

The impact of apolipoprotein E genotypes on age at onset of symptoms and phenotypic expression in Wilson's disease

Abstract: Wilson's disease is a disorder of biliary copper excretion that may result in severe neurological symptoms and advanced liver disease. The wide variation of phenotypic disease expression cannot be fully explained by the different mutations of the Wilson disease gene. In neurological disorders, such as Alzheimer's disease, temporal lobe epilepsy and cerebral trauma, the presence of the apolipoprotein E (ApoE) allele epsilon4 is associated with an increased vulnerability of the brain to the effects of the diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
65
1
9

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(80 citation statements)
references
References 25 publications
5
65
1
9
Order By: Relevance
“…By contrast, studies on WD patients with a common mutation in a given population have not shown this degree of concordance between genotype and phenotype. In a study on patients mainly from Austria, neurological presentation was significantly more common than hepatic presentation in H1069Q homozygotes compared to H1069Q compound heterozygotes or H1069Q negative patients [11] . However, these findings were not borne out by studies from other parts of Europe and North America [4,16] .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…By contrast, studies on WD patients with a common mutation in a given population have not shown this degree of concordance between genotype and phenotype. In a study on patients mainly from Austria, neurological presentation was significantly more common than hepatic presentation in H1069Q homozygotes compared to H1069Q compound heterozygotes or H1069Q negative patients [11] . However, these findings were not borne out by studies from other parts of Europe and North America [4,16] .…”
Section: Discussionmentioning
confidence: 96%
“…It is possible that some of the differences in phenotype between father and son in this family could be due to longstanding untreated copper overload state in the father. Defining disease onset accurately in WD is difficult and this could be a confounding factor in genotype phenotype correlation in WD [11] . I n sum m a r y, we fo un d g en o typ e p h en otype concordance in four families with different types of ATP7B mutations in each family: homozygous exonic mutation in two families, homozygous intronic mutation (Family 3) and compound heterozygous mutation (Family 4).…”
Section: Discussionmentioning
confidence: 99%
“…The lack of consensus in the literature regarding this issue could be explained by the observations that clinical manifestations of WD are heterogeneous even in patients carrying the same mutation. It is, therefore, hypothesized that other additional genetic and/or environmental factors could influence the phenotypes of WD, such as dietary cooper intake, metallothionein inducibility, the individual capacity to handle copper overload, the ApoE genotype, human prion gene polymorphism and mutations in COMMD1 6,17,[19][20][21][22] .…”
mentioning
confidence: 99%
“…The first is the small number of patients included and the further limited number of SNPs analyzed. However, it should be noted that WD is a rare disease, and the number of patients in our study is very similar to that in many other WD or DRD2 gene polymorphism studies (Schiefermeier et al 2000;Kishida et al 2004). This is the first pilot study of DRD2 gene polymorphism in WD, so we tried to assess the most important DRD2 SNPs in neuropsychiatric disorders (especially movement disorders).…”
Section: Drd2 Ex 8 (A/a Vs A/g and G/g)mentioning
confidence: 57%
“…Although these differences remain largely unexplained, several factors are known to impact clinical presentation of WD, including gender (Schilsky et al 1994;Litwin et al 2012a) and genotype (Stapelbroek et al 2004;Gromadzka et al 2005Gromadzka et al , 2006. It is also suspected that WD presentation may be influenced by polymorphisms in the genes encoding prion-related protein, methylenetetrahydrofolate reductase, interleukin-1 receptor antagonist, and apolipoprotein-E Gromadzka et al 2011a, b;Schiefermeier et al 2000;Litwin et al 2012b). Other genes like antioxidant-1 (Atox-1), copper metabolism gene MURR1 domain containing proteins (COMMD), and X-linked inhibitor of apoptosis (XIAP) (Simon et al 2008;Weiss et al 2006;Burstein et al 2005;Weiss et al 2010) have also been suggested as WD modifiers.…”
Section: Introductionmentioning
confidence: 99%